Bjerknes Forces in Motion: Long‐Range Translational Motion and Chiral Directionality Switching in Bubble‐Propelled Micromotors via an Ultrasonic Pathway. (10th October 2017) - Moo, James Guo Sheng; Mayorga‐Martinez, Carmen C.; Wang, Hong; Teo, Wei Zhe; Tan, Beng Hau; Luong, Trung Dung; Gonzalez‐Avila, Silvestre Roberto; Ohl, Claus‐Dieter; Pumera, Martin
Abstract: Manipulation of a micromotor's locomotion has been the ultimate aim of scientists and engineers alike. While numerous roadmaps have been cast, the interswitching of the locomotion and directionality of these miniaturized machines remains elusive. In this report, ultrasound is utilized to produce stop/go motion on bubble‐propelled micromotors via Bjerknes forces. An intricate study using high‐speed camera on the interactions between the bubbles and micromotor is undertaken. The reciprocal action between oscillating bubbles aggregates and ejected microbubbles in an acoustic field demonstrate influence on the motion of the micromotor. Long‐range translational motion can be induced into the micromotor, when repulsive forces between bubble aggregates and ejected microbubbles are manifested in an acoustic field by Bjerknes forces. Additionally, such ultrasonic pulses demonstrate capability to change the directionality of the micromotor, where chirality of the locomotion can be switched. Here, introduction of pulses of ultrasonic irradiation demonstrates new capabilities to switch the motion of bubble‐propelled micromotors. Abstract : Under ultrasound irradiation, the vibration of bubbles in solution results in the manifestation of Bjerknes forces in an acoustic field. Such forces allow for the occurrences of both repulsive and attractive forces, being dependent on the bubble sizes. This paves the way for the manipulation of bubble‐propelled micromotors, where stop‐go, translational, and chiral‐directional motion can be induced.